Inhibition study of rabbit liver cytosolic reductases involved in daunorubicin toxication - Mertlíková-Kaiserová, Helena; Kvasničková, Eva (Journal of enzyme inhibition and medicinal chemistry, 2005)
Anthracycline cardiotoxicity represents the most unfavorable side effect of these highly efficient anticancer drugs. Several biotransformation enzymes have been described to contribute to their cardiotoxicity. Besides the activities of CYP450 isoforms which lead to the generation of reactive oxygen species (ROS), the cytosolic reductases have attracted attention nowadays. The reductases known to metabolize anthracyclines to C13-hydroxyanthracyclines are carbonyl reductase (CR, 1.1.1.184) and the aldo-keto reductases (AKR1C2, 1.3.1.20; AKR1A1, 1.1.1.2). Their participation in the formation of the toxic C13-hydroxymetabolite has been investigated in rabbit using diagnostic inhibitors of CR and AKR1C2. The kinetics and the type of reductase inhibition exerted by the two inhibitors have been described and it was found that CR was the main daunorubicin reductase at both optimal and physiological pH with the kinetic parameters for daunorubicin reduction of Km = 17.01 +/- 1.98 microM and V(max) = 139.60 +/- 5.64 pcat/mg. The IC50 values for quercitrin and flufenamic acid were 5.45 +/- 1.37 microM and 3.68 +/- 1.58 microM, respectively. The inhibition was uncompetitive for both inhibitors and irreversible in the case of flufenamic acid.
Keywords: Rabbits; oxidoreduktasy; Molecular Structure; zvířata; Financing, Organized; financování organizované; cytosol; mužské pohlaví; koncentrace vodíkových iontů; daunomycin; inhibiční koncentrace 50; Kinetics; kinetika; Liver; Inhibitory Concentration 50; Cytosol; Animals; Daunorubicin; králíci; Oxidoreductases; játra; Male; Hydrogen-Ion Concentration; molekulární struktura